A hemicellulose-first approach: one-step conversion of sugarcane bagasse to xylooligosaccharides over activated carbon modified with tandem plasma and acid treatments. Issue 19 (6th July 2022) - Rahmati, Shahrooz; Atanda, Luqman; Horn, Michael; Athukoralalage Don, K. Deshan; Jimenez Forero, Javier; Moghaddam, Lalehvash; Dubal, Deepak; Ostrikov, Kostya (Ken); Doherty, William O. S.
Abstract : Selective depolymerization of sugarcane bagasse to various xylose oligomers using a hybrid of plasma-acid treated activated carbon. Abstract : With growing awareness of a circular economy, it is necessary to utilize all lignocellulose biomass components as a resource to maintain sustainability. We have selectively targeted the one-step conversion of hemicellulose in sugarcane bagasse to xylooligosaccharides (XOS), which are useful dietary supplements, while keeping the cellulose and lignin relatively intact. In addition to the circular economy and green processing chemistry, we pursue plasma treatment of carbon materials as a global effort to produce metal-free carbon-based catalysts. Herein, activated carbon (AC) was subjected to two different treatments: plasma irradiation to create a porous honeycomb structure and redistribute surface oxygenate functional groups (phenolics –OH), lactonics, and (–COOH) and acid impregnation with HNO3 to enhance the overall acidic functional groups of the carbon, especially the –COOH groups. The functionalized AC was effective to selectively depolymerize sugarcane bagasse hemicellulose to XOS in water as a solvent. High XOS yields of 50.0% (composed of xylobiose (14.1%), xylotriose (11.9%), xylotetraose (8.8%), xylopentaose (9.1%) and xylohexaose (6.0%)), and 15% xylose were obtained. No undesirable sugar degradation products – furans – were detected. Thus, we propose that the tandem sequence of plasma and acid modification of AC is a facile one-step new method to depolymerize hemicellulose from lignocellulosic biomass.